Everything and nothing: A critical review of the “social” in Innovation and Entrepreneurship studies - Sardo, Stefania; Callegari, Beniamino; Misganaw, Bisrat A. (NOvation — Critical Studies of Innovation, 2023)
Over the past two decades we have witnessed growing academic and policy interest in phenomena such as social innovation and social entrepreneurship. In these instances, the “social” element has often been described as a new or rediscovered category, indicating a normative predisposition to “elevate” existing or emerging innovation and entrepreneurship processes by identifying and promoting socially-acceptable standards of behavior and goal-setting. While previous reviews on social innovation have focused on the historical development of the concept and its role in academic debate, this article critically reviews the place of the “social” in current mainstream Innovation and Entrepreneurship (I&E) studies. The aim is to understand how this literature has been evolving in relation to this element and to what extent this addition has promoted a radical shift in the research direction. Our review, based on selected articles from 16 I&E mainstream journals, advances a novel classification of the dominant approaches to the social dimension in I&E studies, identifying four main categories: disciplinary, integrationist, separationist, and essentialist. What emerges is that most I&E studies ignore, minimize, or compartmentalize the “social”, using it to extend existing frameworks rather than to evolve them. Indeed, while the “social” has been offering an avenue for critical views to challenge mainstream discourse, at present it does not seem to significantly affect the latter’s evolution.